Pengaruh Struktur Modal dan Kinerja Keberlanjutan Terhadap Nilai Perusahaan pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of capital structure and sustainability performance on firm value in property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The population of this study consisted of property and real estate companies listed on the Indonesia Stock Exchange. Based on the predetermined criteria, the sampling method used was purposive sampling. The final research sample consisted of 43 companies with a total of 215 observations. The hypotheses were tested using multiple linear regression analysis with SPSS 26. Capital structure was measured using the Debt to Equity Ratio (DER), sustainability performance was measured using the Global Reporting Initiative (GRI) index, and firm value was measured using Price to Book Value (PBV). The results of this study indicate that capital structure has a positive and significant effect on firm value, while sustainability performance has a negative but insignificant effect on firm value. Furthermore, capital structure, sustainability performance, firm size, profitability, and sales growth simultaneously have a significant effect on firm value